2020
DOI: 10.1093/ndt/gfaa142.p1791
|View full text |Cite
|
Sign up to set email alerts
|

P1791hla Desensitization- Indian Experience

Abstract: Background and Aims There are many barriers to kidney transplant and one of them is presence of donor specific antibodies (DSAs) in the recipients. Presence of strong DSA is considered a relative contraindication for kidney transplantation, however, if DSAs are of weak to moderate then desensitization is attempted in many centres with good success rate. Desensitizing such patients can be an acceptable approach to increase the donor pool and facilitating transplants. This is a retrospective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The outcomes reported in the present study are similar to those reported previously from other centers in the country. Interestingly, the desensitization protocols used though not same, are quite similar to the ones used at the present center 43‐50 …”
Section: Discussionmentioning
confidence: 83%
“…The outcomes reported in the present study are similar to those reported previously from other centers in the country. Interestingly, the desensitization protocols used though not same, are quite similar to the ones used at the present center 43‐50 …”
Section: Discussionmentioning
confidence: 83%